An Exploratory Factor Analysis (EFA) for Developing and Validating a Scale of Public Acceptance on Willingness to Pay (PAWP) Maximum Demand (MD) Charge in Malaysia - Abdullah, WMZW; Zainudin, WNRA; Ramli, NA (Amer Scientific Publishers, 2024)
Non-Indexed Publication